A Mayan calendar-inspired cyclical TRIZ approach: Enhancing systematic innovation and long-term problem-solving - Altun, Koray (Society of Sytematic Innovation, 2025)
This paper introduces the Mayan calendar-inspired cyclical theory of inventive problem solving (TRIZ) model, an innovative approach to systematic innovation (SI) that integrates the seven TRIZ pillars into a structured model consisting of “Tzolk’in” (short-term, adaptation), “Haab” (mid-term, harmonization), and “Long Count” (long-term, transformation) cycles. Unlike traditional linear innovation models, this cyclical model enables continuous adaptation, iterative refinement, and sustainable evolution. Each cycle addresses a different level of complexity: The adaptation cycle focuses on rapid, low-cost improvements using available resources. The harmonization cycle resolves deep-rooted contradictions to enhance system functionality. The transformation cycle drives strategic evolution by integrating intelligence and automation. This approach is validated through its alignment with trends of engineering system evolution, demonstrating that innovation naturally progresses through these phases. The model’s practical applicability is illustrated through case studies on coffee machine design and automotive seat design, showing how short-term enhancements, mid-term optimization, and long-term transformation collectively contribute to sustainable evolution. By bridging systematic problem-solving with iterative adaptation, the cyclical TRIZ model provides a versatile and scalable SI model for industries seeking to achieve both immediate efficiency gains and long-term innovation resilience. © 2025, Society of Sytematic Innovation. All rights reserved.
Keywords: Cyclical TRIZ Model; Mayan Calendar; Systematic Innovation; TRIZ